PENGGUNAAN CHLORHEXIDINE UNTUK PEMASANGAN DAN PERAWATAN KATETER URIN DALAM MENCEGAH CAUTI: A SCOPING REVIEW - Rajab, M Alfian; Tahir, Takdir; Yusuf, Saldy; Risnah, Risnah (Universitas Islam Negeri Alauddin Makassar, 2023)
Prevention of catheter-associated urinary tract infections (CAUTI) can be done with simple initiatives such as catheter insertion and care can contribute to preventing infection, chlorhexidine is one of the commonly used antiseptic agents due to its cationic molecular nature with various antimicrobial activities, however, until now the choice of the concentration of the use of chlorhexidine is still a polemic in its use. Therefore, the aim of this review is to evaluate the use of chlorhexidine before urinary catheter insertion and treatment in preventing CAUTI. Manual reference searches were carried out using the scoping review method, through the PubMED, DOAJ, Science direct, EBSCO, ProQuest, Garuda, and Gray Literature databases (google scholar). The study was included based on PCC criteria (Population: patients with urinary catheters, Concept: Chlorhexidine use, Context: urinary catheter insertion and care), published from 2011-2021. A total of 171 studies were screened, the remaining eleven articles that met the inclusion criteria and were included in this review. Based on the results of the study found the use of Chlorhexidine with various concentrations, namely 0.05%, 0.1%, 0.5%, 0.9%, 2%, and 4% with various intervention uses, namely, SRV (sustained-release varnishes), periurethral cleaning before catheterization , cleaning urine bag, and bathing Chlorhexidine. The application of the use of chlorhexidine with a concentration of 0.5% - 4% is one of the strategies to prevent CAUTI at the time of insertion and treatment of urinary catheters, especially in the intensive care room.